The UPAYA MENGURANGI PERILAKU MEMBOLOS PADA SISWA KELAS VIII SMP NEGERI 18 PALU MELALUI LAYANAN KONSELING KELOMPOK - Bau Ratu; Ridwan Syahran; Muh. Mansyur Thalib; Ningsih Ningsih (Institut Agama Islam Negeri Kerinci, Indonesia, 2023)
The problem of student truancy behaviour is a problem that often occurs in schools today. Efforts are being made to reduce truancy behaviour by using group counselling services because the primary function of group counselling services is the problem alleviation function. This study aims to increase students' understanding of behaviour, which has negative consequences for themselves and others, and to reduce truant behaviour through group counselling. The type of research used is Guidance and Counseling Action Research with the object of studying 12 class VIII students of SMP Negeri 18 Palu in the 2023/2024 academic year consisting of 10 males and two females, and the research subjects were guidance and counselling teachers. The data collection technique in this study was to use inventory, interview guidelines, observation guidelines, and documentation. The data analysis technique is an interactive model presented as qualitative research. The study results revealed that truant behaviour in class VIII students of SMP Negeri 8 Palu after attending group counselling services was lower than before attending group counselling services.